High Prevalence of Hypocalcemia in Non-severe COVID-19 Patients: A Retrospective Case-Control Study - Pal, Rimesh; Ram, Sant; Zohmangaihi, Deepy; Biswas, Indranil; Suri, Vikas; Yaddanapudi, Laxmi N.; Malhotra, Pankaj; Soni, Shiv L.; Puri, Goverdhan D.; Bhalla, Ashish; Bhadada, Sanjay K. (Frontiers in Medicine, 2021)
PURPOSE To compare serum total calcium and phosphate levels in patients with non-severe COVID-19 with age, sex, and serum 25-hydroxyvitamin D level matched healthy adult cohort. METHODS In this retrospective case-control study, medical records of patients (≥18 years) diagnosed as non-severe COVID-19 admitted at and discharged from our tertiary care institution during the period from April 10, 2020 and June 20, 2020 were retrieved. Baseline investigations, notably, serum calcium, phosphate, albumin, magnesium, 25-hydroxyvitamin D, and C-reactive protein (CRP), were performed at admission before any form of calcium or vitamin D supplementation were considered. The biochemical parameters were compared with age, sex, and 25-hydroxyvitamin D matched healthy adult controls (1:1 ratio) derived from the Chandigarh Urban Bone Epidemiological Study (CUBES). RESULTS After exclusion, 72 patients with non-severe COVID-19 (63 mild and 9 moderate disease) and an equal number of healthy controls were included in the final analysis. Age, sex, serum 25-hydroxyvitamin D, and albumin levels were matched between the 2 groups. Hypovitaminosis D and hypocalcemia were seen in 97% and 67% of the patients, respectively. The patients had lower serum calcium (P value <0.001) and phosphate (P value=0.007) compared with the controls. There was no statistically significant correlation between serum calcium and CRP. CONCLUSIONS Hypocalcemia is highly prevalent even in COVID-19 patients with non-severe disease probably implying that hypocalcemia is intrinsic to the disease. Prospective studies with larger number of patients are required to prove this hypothesis and unravel the underlying pathophysiological mechanisms.